Stacked denoising autoencoder based fault location in voltage source converters‐high voltage direct current - Luo, Guomin; Cheng, Mengxiao; Hei, Jiaxin; Wang, Xiaojun; Huang, Weibo; He, Jinghan (IET generation, transmission & distribution, 2021)
High voltage direct current has been more and more popular in modern transmission systems. Accurate fault location could help fault clearance and fast recovery of the faulted system. A stacked denoising autoencoder based fault location method for high voltage direct current transmission systems is proposed. The local measurements are analysed, and an end‐to‐end stacked denoising autoencoder‐based fault location is realised. Representative features are extracted with unsupervised learning and labelled as the input of the regression network for fine‐tuning in a supervised manner. The trained network can precisely map the local measurements and their corresponding fault distance. The performance of the proposed method is tested on a point‐to‐point high voltage direct current transmission system, which is modelled on the platform of PSCAD/EMTDC. The faults on both overhead lines and cables are considered, and the location performance in different scenarios are discussed. The simulation results show that the proposed method is effective in pinpointing faults location in various cases.